2019
DOI: 10.1177/0002764219835247
|View full text |Cite
|
Sign up to set email alerts
|

Temp Nations? A Research Agenda on Migration, Temporariness, and Membership

Abstract: This article outlines a research agenda to study how, why, and with what consequences systems of migration policy that rely on time-delimited statuses have been tools of nation-state making. Taking a long view and comparing key contemporary cases, I argue that temporary migration regimes have been appealing because they purport to reconcile the disparate interests and preferences of political actors in sending and receiving countries, native and foreign workers, and employers. Such regimes have been a means fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…In a historical context of growing diversification of migration channels and legal statuses for highly killed immigration, it is necessary to disaggregate legal immigration in an analysis that pays attention to the complexification of visa policies between temporary and permanent, the different legal tracks that this entails and the rights attached to each legal track (Gonzales & Sigona, 2017;Cook-Martín, 2019). Visa policies for highly skilled immigrants are not only formal or administrative instruments the United States uses to determine who enters the country and under what conditions, but they also function as technologies of control and regulation of labour at a macro and micro level.…”
Section: Comple Xific Ation Of Visa P Olicie S and Immig R Ants' Prec...mentioning
confidence: 99%
“…In a historical context of growing diversification of migration channels and legal statuses for highly killed immigration, it is necessary to disaggregate legal immigration in an analysis that pays attention to the complexification of visa policies between temporary and permanent, the different legal tracks that this entails and the rights attached to each legal track (Gonzales & Sigona, 2017;Cook-Martín, 2019). Visa policies for highly skilled immigrants are not only formal or administrative instruments the United States uses to determine who enters the country and under what conditions, but they also function as technologies of control and regulation of labour at a macro and micro level.…”
Section: Comple Xific Ation Of Visa P Olicie S and Immig R Ants' Prec...mentioning
confidence: 99%
“…This means that the various government authorities interact with them differently (Coutin 2000). Temporary status, coupled with the threat of deportation, reduces the bargaining power of migrant workers vis-à-vis employers, thereby increasing their vulnerability to exploitative labour, debt relationships, and dependence on labour contractors (Cook-Martin 2019;Shamir 2017). It also gives rise to experiences of discrimination and exclusion, a fragmented sense of belonging, and transnational families (Menjívar 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They cannot bring family members, cannot easily change employers, and have no pathways to permanent settlement. These regulations are particularly strict in migrant-receiving countries in Asia as compared with Western liberal democracies (Castles et al, 2014; Cook-Martin, 2019; Stasiulis, 2008; Tong and Jiang, 2020).…”
Section: Research On Migrant Differentiationmentioning
confidence: 99%
“…For example, most Asian countries regard labor migration as a temporary necessity and regulate it to ensure that the recruitment of foreign labor, particularly low-skilled labor, will not lead to permanent settlement (Castles et al, 2014: 156). Differentiating migrants based on skill levels, ethnicity, and other parameters are also common among Western countries (Cook-Martin, 2019). A study of the United States of America (USA) and five major European countries found that the social rights of migrants varied by entry category and that migrants did not have the same social rights as native citizens (Sainsbury, 2012).…”
Section: Introductionmentioning
confidence: 99%